Increased Progesterone/Estradiol Ratio on the Day of hCG Administration Adversely Affects Success of In Vitro Fertilization-Embryo Transfer in Patients Stimulated with Gonadotropin-releasing Hormone Agonist and Recombinant Follicle-stimulating Hormone - Yu-Che Ou; Kuo-Chung Lan; Shiuh-Young Chang; Fu-Tsai Kung; Fu-Jen Huang (Elsevier, 2008)
Objective: We investigated the influence of premature luteinization in in vitro fertilization using a long protocol of gonadotropin-releasing hormone agonist (GnRHa) and recombinant follicle-stimulating hormone (rFSH), taking ovarian response into account in the definition of premature luteinization. Materials and Methods: A total of 339 cycles of controlled ovarian hyperstimulation with rFSH and GnRHa were performed in 311 infertile couples. Premature luteinization was defined as a progesterone (P) to estradiol (E2) ratio of > 1 on the day of human chorionic gonadotropin (hCG) administration. The P/E2 ratio is calculated as: P (ng/mL) × 1,000/E2 (pg/mL). Clinical outcomes were compared for the prematurely luteinized and non-prematurely luteinized groups. Results: The mean number of retrieved oocytes, recovered mature oocytes, embryos and top quality embryos were significantly higher in the non-prematurely luteinized group than in the prematurely luteinized group. Although fertilization rates and implantation rates were similar between the two groups, the clinical pregnancy rate was higher in the non-prematurely luteinized group than in the prematurely luteinized group. Conclusion: Premature luteinization, defined as late follicular P/E2 ratio of > 1 in long GnRHa cycles with rFSH stimulation, adversely affected ovarian responses and clinical outcomes. It seems unrelated to preovulatory luteinizing hormone (LH) elevation and LH/hCG content of gonadotropins and could be associated with poor ovarian response and the presence of dysmature follicles. [Taiwan J Obstet Cynecol 2008;47(2):1 68-1 74]